Exploring Value Cocreation in Relationships Between an ERP Vendor and Its Partners: A Revelatory Case Study1 - Sarker, Suprateek; Sarker, Saonee; Sahaym, Arvin; Bjørn-Andersen, Niels (MIS Quarterly, 2012)
Contemporary business organizations are increasingly turning their attention to jointly creating value with a variety of stakeholders, such as individual customers and other business organizations. However, a review of the literature reveals that very few studies have systematically examined value cocreation within business-to-business (B2B) contexts. Using a revelatory case study of the relationship between an ERP vendor with a global reputation and its partners, and informed by the resource-based view of the firm and related theoretical perspectives, we develop an understanding of value cocreation in B2B alliances associated with selling, extending, and implementing packaged software, specifically ERP systems. Our study reveals that there are different mechanisms underlying value cocreation within B2B alliances, and also points to several categories of contingency factors that influence these mechanisms. In addition to providing insights about the phenomenon of cocreation itself, the study contributes to the stream of packaged software literature, where the implications of value cocreation in alliances between packaged software vendors and their partners for the client organizations have not been sufficiently explored.